Oncorhynchus mykiss silage improves meat fatty acids profile, blood parameters, intestinal histomorphometry, productive performance, and modulates the cecal microbiota of Cavia porcellus - Arista, Miguel; Zamora-Huamán, Segundo José; Saucedo-Uriarte, José Américo; Fernandez-Castro, Paul; Maldonado, Niger; Valle, Loidy; Del Solar, Jakson Ch.; Arista Vargas, Diana L.; Lopez Lapa, Rainer M.; Torres, Carlos; Leiva, Yoany; Vásquez, Héctor V.; et al. (Frontiers in Nutrition, 2026)
The use of rainbow trout silage represents an alternative for the feeding of domestic species such as guinea pigs with a circular economy approach. The objective of this study was to evaluate the effect of Oncorhynchus mykiss silage in the diet of Cavia porcellus on the fatty acid profile of the meat, blood parameters, intestinal histomorphometry, productive performance, and cecal microbiota. Thirty-three weaned male guinea pigs of the Peru breed were used, distributed in three treatments: T0 (0%), T1 (4%), and T2 (8% silage inclusion in the diet), with 11 replicates each. The inclusion of silage in the diets significantly modified the lipid profile of the meat, increasing monounsaturated fatty acids and docosahexaenoic acid (DHA, C22:6) (p < 0.001) compared to T0. No changes were observed in most hematological and biochemical parameters, with the exception of mean platelet volume (MPV) (p = 0.020) and total cholesterol (TC) (p < 0.001). Higher silage inclusion favored the development of crypt depth (p = 0.047). The alpha diversity of cecal microbiota did not vary (p > 0.05), but beta diversity revealed compositional changes associated with silage consumption (Bray–Curtis, p = 0.006; Jaccard, p = 0.017). Productive performance, such as weight gain increased in T2 (p = 0.050) and feed conversion factor, decreased with silage inclusion (p < 0.001), without affecting intake. In conclusion, trout silage represents a sustainable alternative ingredient in the use of fish by-products that improves the nutritional quality of guinea pig meat and optimizes feed efficiency, without compromising animal health or performance.